أبو سعد الإدريسي الإستراباذي: مؤرخ تاريخ سمرقند - الشمري، ظفار قحطان عبدالستار (جامعة بغداد - كلية الآداب, 2022)
لقد كان للعرب دور حضاري في سمرقند من الفتح العربي الإسلامي حتى نهاية القرن الثالث الهجري / التاسع الميلادي مما له الأثر الكبير في اختيار هذه الدراسة لما حملت كتب الطبقات والتراجم طائفة كبيرة من حملة العلوم والثقافة في بلاد ما وراء النهر عامة وسمرقند خاصة في القرن الرابع والخامس الهجريين / العاشر والحادي عشر الميلادي حيث ظهر المحدثون والفقهاء والأدباء وغيرهم .... وتضمنت معلومات قيمة عن المدارس والمساجد والربط وخزائن الكتب، ولما يتمتع إقليم سمرقند وموقعه من الفكر العربي مكانة مرموقة في الدولة العربية الإسلامية على الرغم من بعدها عن المركز حيث كان يتركز في ضمير العلماء العرب الذين اندفعوا بكل حيوية إلى بناء هذا الصرح الفكري حيث استمرت الحركة الفكرية العربية في سمرقند تؤتي ثمارها في القرن الرابع الهجري وبعده من حيث الابتكار وكمية الإنتاج وتنوعه في الأدب والعلوم المختلفة. Samarkand is considered one of the provinces of Transoxiana, and it was able under the shadow of the Arab Islamic state to rise in a great renaissance in cultural, literary and scientific life that appeared clearly in the fourth century AH, represented by an elite of scholars, jurists, historians, and writers such as Abu Saad Al-Idrisi Al-Astrabadi, historian of the history of Samarkand and others who contributed a great deal. Abundant in the awakening of the nation in that historical era. The study showed the emergence of books that placed the human sciences, including in the histories of Samarkand in the fourth and fifth centuries AH. The Samarqand history blogger is considered one of the important sources that many historians have borrowed from, such as Al-Khatib Al-Baghdadi and others who provided us with important information and basic sources on the translations of the Samarqand. There is no doubt that a number of Baghdad scholars have borrowed from it from its men and scholars and mentioned their lineage, sheikhs, students, place and dates of their deaths, as al-Khatib translated it based on the history of Samarkand by al-Idrisi.
Keywords: الإستراباذي، عبدالرحمن بن محمد بن عبدالله الإدريسي، ت. 504 هـ. -- الفتوحات الإسلامية -- تراحم المؤرخون -- تاريخ سمرقند